Analisis Literasi Keuangan dan Duta Pasar Modal Bursa Efek Indonesia Bagi Pelajar SMAN 2 Jombang - Verlandes, Yuliasnita; Hadi Purnomo, Agoes; Nersiwad, Nersiwad; Baidlowi, Imam (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The results of opening the Capital Market Ambassador accounts for the students of SMAN 2 Jombang, as the only Investment Gallery for Education in Jombang Regency. This activity aims to improve capital market literacy and inclusion by ensuring that the community spreads information about the world of investment in the capital market. This research was conducted in Jombang Regency in collaboration with the East Java Representative of the Indonesia Stock Exchange (IDX) on October 23, 2024, with the main focus being the students of SMAN 2 Jombang, as the sole owner of the Educational Investment Gallery in Jombang Regency.